The Positive Obligations of the State under the European Convention of Human Rights. - Xenos, Dimitris (Routledge research in human rights law., 2012)
The system of the European Convention of Human Rights imposes positive obligations on the state to guarantee human rights in circumstances where state agents dot not directly interfere. In addition to the traditional/liberal negative obligation of non-interference, the state must actively protect the human rights of individuals residing within its jurisdiction. The liability of the state in terms of positive obligations induces a freestanding imperative of human rights that changes fundamentally the perception of the role of the state and the participatory ability of the individual, who can.